Facile construction of mitochondria-targeting nanoparticles for enhanced phototherapeutic effects. (29th March 2017) - Liu, Yi; Li, Heping; Xie, Jin; Zhou, Mengxue; Huang, Hui; Lu, Huiru; Chai, Zhifang; Chen, Jun; Hu, Yi
Abstract : An illustration of the preparation of ICG/rPAA@SWCNT nanoparticles which target mitochondria for amplifying photodynamic therapeutic effects. Abstract : Phototherapy, as a noninvasive therapeutic procedure, has been applied to treat tumors. However, the application of phototherapy is often compromised by its low efficiency. Herein, we developed a novel nanoplatform based on cationic amphiphilic polymer-wrapped carbon nanotubes (rPAA@SWCNTs) with a photosensitizer, indocyanine green (ICG), for phototherapy. The as-prepared nanoparticles exhibited excellent mitochondria targeting due to the synergistic properties of highly positive charges from the polycations on the corona and the high hydrophobicity from the carbon nanotubes in the core. Moreover, the high buffer capacity of the polycations facilitated the endosomal escape of nanoparticles via a proton-sponge effect. When irradiated with an 808 nm NIR laser, ICG/rPAA@SWCNTs could precisely damage mitochondria with high efficiency and produce reactive oxygen species (ROS) and hyperthermia, which further induced the ROS burst from damaged mitochondria. The overproduced ROS accumulated in mitochondria ultimately resulted in mitochondrial damage and cell death. Therefore ICG/rPAA@SWCNTs may be able to achieve an amplifying phototherapeutic effect.